Development Criteria of Auto pedagogic Competence - Gulnora Oblakulovna Ernazarova (Academia One Publishing, 2023)
in this article, the formation of an auto pedagogic competence of a teacher is closely related to the development of an innovative educational environment, it isformed in the process of general pedagogical preparation for professional activity, according to scientists, auto psychological competence is associated with the concept of professional self-awareness, selfknowledge and self-realization.-development, it is important in the process of professional formation, questions
Keywords: auto pedagogic competence; professional activity; professional self-awareness